A Coal Bump Risk Assessment and Prediction Model Based on Multiparameter Indices. (16th March 2022) - Luo, Tao; Fan, Gangwei; Zhang, Shizhong; Ren, Shang; Fan, Yibo; Shen, Ruiliang
Abstract : Coal bump, a common dynamic disaster in mining of deep coal resources, its assessing and predicting is an important component in safety management. This paper presents a model to assess and predict coal bump risk based on multiparameter indices. A new energy accumulation index S was proposed by considering acoustic emission and electromagnetic emission signal characteristics in mine shocks. Combined with indices E (energy of microseisms) and N (frequency of microseisms) of microseismic monitoring, a static and dynamic coal bump risk assessment and prediction model was established. We studied coal bump events that occurred during extraction in 311305 working face of Bayangale coal mine in Inner Mongolia, China. We obtained the acoustic emission and electromagnetic emission signal distribution and change law, using principal component analysis method and density ellipse to establish the index S . A typical precursory of coal bumps is that AE and EME strength has obvious fluctuation period of 3-4 days, index S showing an obvious decreasing trend, while the time-series curve of the microseismic energy is relatively stable, and the vibration frequency curve has a significant upward trend. After predict the potential coal bump risk and its area of occurrence, large diameter drilling ( Φ 150 mm) on-site was used to relief pressure concertation in coal seam and roof. The results demonstrate that this model based on multiparameter indices is capable of quantitatively prewarning rock burst risk.